2006
DOI: 10.1111/j.1365-2265.2006.02602.x
|View full text |Cite
|
Sign up to set email alerts
|

Profile, mean residence time of ACTH and cortisol responses after low and standard ACTH tests in healthy volunteers

Abstract: The elimination rate of ACTH in healthy volunteers was significantly lower in LDT than in HDT, but cortisol production rate appears to be identical in both tests, so that a maximum adrenal stimulation seems to exist. The use of LDT may be more adequate, although data from patients need studying.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…In a normal individual, an intravenous bolus of ACTH 1-24 disappears from the circulation with a half-life of about 5 min and is eliminated from the circulation rapidly, followed after a delay of 15-30 min later with a sustained secretion of cortisol. Small versus large doses of tetracosactin stimulate the same cortisol production rate, i.e., the same peak level of cortisol and area under the curve (Alia et al, 2006). Simultaneously, a single bolus of this peptide activates the prolonged synthesis of enzymes involved in steroidogenesis (Lehoux et al, 1998).…”
Section: Molecular Mechanisms Of Tissue-protective Effectsmentioning
confidence: 98%
“…In a normal individual, an intravenous bolus of ACTH 1-24 disappears from the circulation with a half-life of about 5 min and is eliminated from the circulation rapidly, followed after a delay of 15-30 min later with a sustained secretion of cortisol. Small versus large doses of tetracosactin stimulate the same cortisol production rate, i.e., the same peak level of cortisol and area under the curve (Alia et al, 2006). Simultaneously, a single bolus of this peptide activates the prolonged synthesis of enzymes involved in steroidogenesis (Lehoux et al, 1998).…”
Section: Molecular Mechanisms Of Tissue-protective Effectsmentioning
confidence: 98%
“…68 Dorin et al 60 found the synacthen test to have high sensitivity in cases of primary adrenal insufficiency but found no statistically significant difference in sensitivity between the standard-dose (250 mg) and the low-dose (1 mg) tests in secondary adrenal insufficiency. 60 There are conflicting data reporting that the standard-dose (250 mg) synacthen test is more sensitive than the low-dose (1 mg) synacthen test in detecting cases of secondary adrenal insufficiency.…”
Section: Test Comparisonsmentioning
confidence: 99%
“…66,67 Nevertheless the test is challenging to perform, blood concentrations are still supraphysiological and similar diagnostic sensitivities to the standard-dose test were demonstrated by Mayenknecht et al 61 More recently these observations were confirmed by a meta-analysis suggesting that the low-dose test is no more effective than the standard test. 60,68 Using either the low-or standard-dose test, many patients with pituitary disease with marginal responses will require further testing with the insulin tolerance or overnight metyrapone tests. 61 …”
Section: Acth Stimulation Testing (Synacthen Test)mentioning
confidence: 99%
“…Its chronic effects to enhance the gland's steroidogenic enzymes in the biosynthetic pathway and to make more cells capable of conducting steroidogenesis have also been studied (Vinson 2003). Although assessment of adrenal function in human patients for diagnostic purposes is carried out by standardized ACTH tests (Alia et al 2006), there is little direct evidence available for the actions of ACTH on the production of aldosterone in rodents. Aldosterone has primarily been studied in the context of its function within the RAAS.…”
Section: Aldosterone and Acth In Micementioning
confidence: 99%